Method for preparing spherical aluminum hypophosphite with rough surface at low temperature and normal pressure
By using aluminum sulfate hexadecimal and sodium hypophosphate monohydrate under low temperature and normal pressure, combined with ethylene glycol as solvent, controlling the reaction conditions, the morphology and particle size distribution of aluminum hypophosphate were solved, and the efficient preparation of spherical aluminum hypophosphate was achieved. , improving its flame retardant performance and feasibility of modification process.
Patent Information
- Application Number
- CN202411366988.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-14
AI Technical Summary
Among the existing aluminum hypophosphate preparation methods, the product has poor morphology, large particle size and wide particle size distribution, which limits its flame retardant effect and subsequent modification.
Using aluminum sulfate hexadecimal and sodium hypophosphate monohydrate as raw materials, water and ethylene glycol as mixed solvents, the temperature of aluminum sulfate solution dropwise to sodium hypophosphate solution is controlled at low temperature (less than 100 °C) and normal pressure. The amount of ethylene glycol is used to achieve spherical aluminum hypophosphate synthesis without agglomeration and excellent dispersion.
Spherical aluminum hypophosphate was prepared in a regular morphology, narrow particle size distribution and good dispersion, which simplified the process steps, reduced the cost of raw materials, and had the possibility of large-scale industrialization.
Smart Images

Figure CN119306193A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing spherical aluminum hypophosphite with a rough surface under low temperature and normal pressure, belonging to the technical field of polymer flame retardants. Background Art
[0002] The chemical structure and organic components of polymer materials make most of them highly flammable, which greatly limits their practical application in daily life. Therefore, the development of efficient flame retardants is crucial to prevent costly damage caused by accidental fires and protect the health and safety of the public. At present, the types and selections of flame retardants mainly include three categories: inorganic flame retardants, bromine flame retardants, and phosphorus nitrogen flame retardants. Inorganic flame retardants are low in cost and environmentally friendly and harmless, but their poor compatibility with polymer materials leads to a large amount of addition. It is necessary to add more than 30% to the polymer material matrix to achieve a good flame retardant effect. Bromine flame retardants have significant advantages, low cost, high stability, good compatibility with polymer materials, and small addition amount; at the same time, the disadvantages are also very obvious. The combustion of bromine flame retardants will produce toxic smoke and gas, which will damage the body and the environment, and is extremely harmful. Moreover, bromine flame retardants are gradually being banned and replaced, and people need a new type of efficient flame retardant. Phosphorus-nitrogen flame retardants have the advantages of low smoke, non-toxicity, and halogen-free. They are rich in phosphorus content, and have excellent flame retardant effects after the phosphorus and nitrogen elements are compounded. They have little effect on the mechanical properties of the material, are in line with the development direction of flame retardants, and have good development prospects.
[0003] Aluminum hypophosphite belongs to phosphorus-based flame retardants, which have the advantages of low smoke, halogen-free and non-toxic. Its phosphorus content can reach 40%. After being added to polymer materials such as PP, TPU, PBT, it has excellent flame retardant properties, low cost, green and environmentally friendly. It has both condensed phase flame retardant mechanism and gas phase flame retardant mechanism. It is a new flame retardant that can effectively improve the flame retardant properties of polymers.
[0004] The current preparation method of aluminum hypophosphite flame retardant mainly uses soluble aluminum salt and sodium hypophosphite as raw materials to synthesize aluminum hypophosphite through a simple double decomposition reaction. Although the process route is simple, the aluminum hypophosphite synthesized by the company currently has a poor morphology, mostly amorphous morphology, large particle size, and wide particle size distribution.
[0005] In order to solve the above problems, Chinese patent document CN118026115A discloses a method for preparing aluminum hypophosphite with low sulfur content and fine particle size, using aluminum sulfate and sodium hypophosphite as raw materials, adding surfactant sodium dodecylbenzene sulfonate and crystal nucleus MCA as seeds, and synthesized aluminum hypophosphite with a median diameter of 4-5 μm. Although the sulfur content is reduced, there is no fixed morphology, and the addition of excess substances in the system has a certain impact on purity and post-processing. Chinese patent document CN111689481A discloses a method for preparing ultrafine powder of aluminum hypophosphite flame retardant, using aluminum hypophosphite and sodium hypophosphite as raw materials, adding nano titanium dioxide or nano silicon dioxide as a barrier medium, avoiding the agglomeration of aluminum hypophosphite particles, although aluminum hypophosphite with a particle size range of 0.5-5 μm is prepared, but the added additional substances affect the subsequent impurity removal. For example, Chinese patent document CN107337187B discloses a method for preparing nano aluminum hypophosphite, which adopts a microemulsion method to prepare nano-sized aluminum hypophosphite through a microemulsion reactor. However, oil phase solvents and surfactants are added during the reaction, and the reaction conditions are complicated, which is not conducive to the realization of large-scale industrialization.
[0006] In summary, aluminum hypophosphite synthesized by conventional methods currently mostly has irregular morphology, large particle size, and wide particle size distribution. These disadvantages are not conducive to the subsequent modification of aluminum hypophosphite and limit the flame retardant effect of aluminum hypophosphite.
[0007] Therefore, it is of great significance to develop a method for preparing a new type of aluminum hypophosphite with good morphology and narrow particle size distribution without adding additional substances. Summary of the invention
[0008] In view of the shortcomings of the existing preparation of aluminum hypophosphite, the present invention provides a method for preparing spherical aluminum hypophosphite with a rough surface at low temperature and normal pressure.
[0009] The present invention uses aluminum sulfate hexahydrate and sodium hypophosphite monohydrate as raw materials, and water and ethylene glycol as mixed solvents. The experimental process is simple, no additional substances need to be added, and complicated impurity removal steps are avoided. Aluminum hypophosphite is synthesized by double decomposition reaction at a relatively low temperature (less than 100°C) and normal pressure. The synthesis of spherical aluminum hypophosphite with no agglomeration and excellent dispersibility is achieved mainly by controlling the reaction conditions of the temperature when the aluminum sulfate solution is dripped into the sodium hypophosphite solution and the amount of ethylene glycol. The preparation process of the present invention is simple, and the synthesized aluminum hypophosphite product has excellent morphology, narrow particle size distribution, and good dispersibility.
[0010] The microscopic morphology of the spherical aluminum hypophosphite is a spherical structure with a regular morphology and a rough surface formed by stacking small particles.
[0011] The technical solution of the present invention is as follows: A method for preparing spherical aluminum hypophosphite with a rough surface at low temperature and normal pressure comprises the following steps: (1) adding deionized water to aluminum sulfate hexadecahydrate and stirring until the aluminum sulfate hexadecahydrate is completely dissolved to obtain an aluminum sulfate hexadecahydrate aqueous solution; (2) dissolving sodium hypophosphite monohydrate in deionized water and ethylene glycol to prepare a sodium hypophosphite monohydrate solution; (3) Under mechanical stirring conditions, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution at a certain temperature, mix them evenly, and heat the water bath to 90°C. The two react to form aluminum hypophosphite; (4) The prepared aluminum hypophosphite slurry is first washed and centrifuged with deionized water, then washed and centrifuged with anhydrous ethanol, vacuum dried, and ground to obtain spherical aluminum hypophosphite.
[0012] According to the present invention, preferably, in step (1), the concentration of the aluminum sulfate hexadecahydrate aqueous solution is 1.0-3.5 mol / L, preferably 2.0 mol / L.
[0013] According to the present invention, preferably, in step (2), the concentration of the sodium hypophosphite monohydrate solution is 2.85-8.75 mol / L.
[0014] According to the present invention, preferably, the molar ratio of sodium hypophosphite monohydrate to aluminum sulfate hexadecahydrate is 5-7:1, preferably 6:1.
[0015] According to the present invention, preferably, in step (2), the volume ratio of the total amount of deionized water used to the amount of ethylene glycol added is 1:2.
[0016] According to the present invention, preferably, in step (1) and step (2), the volume ratio of the total amount of deionized water used to the amount of ethylene glycol added is (1-1.1125):1, preferably 1:1.
[0017] Adding an appropriate amount of ethylene glycol increases the supersaturation of the growing material, which is conducive to the formation of a large number of crystal nuclei and reduces the size of the product particles. At the same time, ethylene glycol itself has a certain viscosity, which is conducive to the slow and uniform growth of the crystal nuclei, thereby obtaining a uniform spherical morphology.
[0018] According to the present invention, preferably, in step (3), the dropping temperature is 20-40° C., preferably 30° C. When the dropping temperature is lower, the growth rate of the crystal nucleus is slower.
[0019] According to the present invention, preferably, in step (3), the reaction time is 0.5-2 hours, preferably 1 hour.
[0020] According to the present invention, preferably, in step (3), the mechanical stirring speed is 300-450 rpm, preferably 350 rpm.
[0021] The invention uses aluminum sulfate hexadecahydrate and sodium hypophosphite monohydrate as raw materials, controls the particle size and improves the product morphology under low temperature and normal pressure, and synthesizes spherical aluminum hypophosphite with regular morphology and rough surface.
[0022] The technical features and beneficial effects of the present invention are as follows: 1. The present invention uses aluminum sulfate hexahydrate and sodium hypophosphite monohydrate as raw materials, and does not require high temperature and high pressure. By controlling the temperature when the aluminum sulfate hexahydrate aqueous solution is dripped into the sodium hypophosphite monohydrate solution and adding a certain amount of ethylene glycol as a solvent, the product morphology is adjusted at a relatively low water bath temperature to prepare uniform spherical aluminum hypophosphite. The preparation operation is simple, the synthesis steps are simple, the raw material cost is low, and the process can be completed at low temperature (less than 100 ° C) and normal pressure, which has the possibility of realizing large-scale industrialization. By controlling the dripping temperature, the supersaturation of the system is controlled, the crystal nucleation speed and the crystal nucleus growth speed are improved, and the addition at the same time increases the solvent viscosity, which is conducive to the diffusion control growth of the crystal nucleus, and further makes the product size uniform to form uniform spherical particles.
[0023] 2. The method of the present invention is used to prepare aluminum hypophosphite with regular morphology and high spherical yield without adding additional substances. The particle size distribution is narrow and it is conducive to the subsequent modification process of aluminum hypophosphite. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope photo of aluminum hypophosphite.
[0025] Figure 2 This is a transmission electron microscope photo of aluminum hypophosphite.
[0026] Figure 3 This is the XRD pattern of aluminum hypophosphite.
[0027] Figure 4 This is the EDS spectrum of aluminum hypophosphite.
[0028] Figure 5 This is the mapping spectrum of aluminum hypophosphite.
[0029] Figure 6 This is the particle size distribution diagram of aluminum hypophosphite.
[0030] Figure 7 This is a scanning electron microscope photograph of the aluminum hypophosphite of Comparative Example 1.
[0031] Figure 8 This is a scanning electron microscope photograph of the aluminum hypophosphite of Comparative Example 2.
[0032] Fig. 9 This is a scanning electron microscope photograph of the aluminum hypophosphite of Comparative Example 3.
[0033] Fig.10 This is a scanning electron microscope photograph of the aluminum hypophosphite of Comparative Example 4.
[0034] Fig.11 This is a scanning electron microscope photograph of the aluminum hypophosphite of Comparative Example 5. DETAILED DESCRIPTION
[0035] The present invention will be further described below through specific embodiments in conjunction with the accompanying drawings, but is not limited thereto.
[0036] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials used are commercially available unless otherwise specified.
[0037] Example 1 Synthesis of Spherical Aluminum Hypophosphite with Rough Surface S1. Place 11.03 g (17 mmol) of aluminum sulfate hexadecahydrate in a round-bottom flask, add 8.75 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 11.13 g (105 mmol) of sodium hypophosphite monohydrate in a round-bottom flask, add 8.75 mL of deionized water and 17.5 mL of ethylene glycol, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 30°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 1 hour at a mechanical stirring speed of 350 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0038] The material synthesized in Example 1 was characterized by Figure 1 SEM images of aluminum hypophosphite and Figure 2 The transmission electron microscope image of aluminum hypophosphite shows that its microscopic morphology presents a well-dispersed, regular spherical structure. Figure 3 The characteristic peaks in the XRD pattern prove that aluminum hypophosphite is successfully synthesized. Figure 4 EDS spectra and Figure 5 The mapping spectrum further confirmed that the product was aluminum hypophosphite. Figure 6 The particle size distribution diagram of aluminum hypophosphite shows that the particle size distribution of the synthesized aluminum hypophosphite is narrow. 10 = 1.53 μm, d 50 =2.52 μm, d 90 = 3.93 μm.
[0039] Example 2 Synthesis of Spherical Aluminum Hypophosphite with Rough Surface S1. Place 22.06 g (35 mmol) of aluminum sulfate hexadecahydrate in a round-bottom flask, add 10 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 22.26 g (210 mmol) of sodium hypophosphite monohydrate in a round-bottom flask, add 8 mL of deionized water and 16 mL of ethylene glycol, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 20°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 2 hours at a mechanical stirring speed of 300 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0040] Example 3 Synthesis of Spherical Aluminum Hypophosphite with Rough Surface S1. Place 6.62 g (11 mmol) of aluminum sulfate hexadecahydrate in a round-bottom flask, add 10 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 8.16 g (77 mmol) of sodium hypophosphite monohydrate in a round-bottom flask, add 9 mL of deionized water and 18 mL of ethylene glycol, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 40°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 0.5 hours at a mechanical stirring speed of 320 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0041] Example 4 Synthesis of Spherical Aluminum Hypophosphite with Rough Surface S1. Place 13.24 g (21 mmol) of aluminum sulfate hexadecahydrate in a round-bottom flask, add 8.75 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 11.13 g (105 mmol) of sodium hypophosphite monohydrate in a round-bottom flask, add 8.75 mL of deionized water and 17.5 mL of ethylene glycol, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 30°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 2 hours at a mechanical stirring speed of 450 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0042] Comparative Example 1 The synthesis of aluminum hypophosphite was as described in Example 1, except that ethylene glycol was not added; The specific steps are as follows: S1. Place 11.03 g of aluminum sulfate hexadecahydrate in a round-bottom flask, add 8.75 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 11.13 g of sodium hypophosphite monohydrate in a round-bottom flask, add 26.25 mL of deionized water, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 30°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 1 hour at a mechanical stirring speed of 350 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0043] Scanning electron microscopy of aluminum hypophosphite of comparative example 1 Figure 7 It shows that the morphology of aluminum hypophosphite prepared without adding ethylene glycol is an irregular flake or block structure, which shows that an appropriate amount of ethylene glycol can optimize the morphology of aluminum hypophosphite.
[0044] Comparative Example 2 The synthesis of aluminum hypophosphite was as described in Example 1, except that: The amount of ethylene glycol added was 8.75 mL.
[0045] Scanning electron microscopy of aluminum hypophosphite of comparative example 2 Figure 8 The results show that the aluminum hypophosphite prepared with 8.75 mL of ethylene glycol has an amorphous block shape and a large particle size of more than 10 μm. If the amount of ethylene glycol added is too little, the dissolution and dispersion of the reactants are insufficient, and the final product has problems such as poor dispersibility and uneven particles. The particles show obvious adhesion and form large clusters. The aluminum hypophosphite finally appears as irregular blocks instead of ideal spherical particles.
[0046] Comparative Example 3 The synthesis of aluminum hypophosphite was as described in Example 1, except that: The amount of ethylene glycol added was 26.5 mL.
[0047] Scanning electron microscopy of aluminum hypophosphite of comparative example 3 Fig. 9 The results show that the aluminum hypophosphite prepared with an addition amount of ethylene glycol of 26.5 mL has a spherical morphology that adheres together. Excessive ethylene glycol can lead to enhanced interactions between particles and increased adhesion, so that the formed particles stick together after the reaction, resulting in poor dispersion of the product. It can be seen that an appropriate amount of ethylene glycol can optimize the morphology of aluminum hypophosphite.
[0048] Comparative Example 4 The synthesis of aluminum hypophosphite was as described in Example 1, except that the temperature when the aluminum sulfate hexahydrate aqueous solution was added dropwise to the sodium hypophosphite monohydrate solution was 60°C.
[0049] The specific steps are as follows: S1. Place 11.03 g of aluminum sulfate hexadecahydrate in a round-bottom flask, add 8.75 mL of deionized water, heat the water bath to 90 °C, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to prepare an aluminum sulfate hexadecahydrate aqueous solution; S2. Place 11.13 g of sodium hypophosphite monohydrate in a round-bottom flask, add 8.75 mL of deionized water and 17.5 mL of ethylene glycol, and stir until the sodium hypophosphite monohydrate is completely dissolved to prepare a sodium hypophosphite monohydrate solution; S3. At 60°C, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution while stirring, mix evenly, raise the temperature to 90°C, and react for 1 hour at a mechanical stirring speed of 350 rpm. After centrifugal washing and drying, aluminum hypophosphite is obtained.
[0050] Scanning electron microscopy of aluminum hypophosphite of comparative example 4 Fig.10 The results show that when the temperature of aluminum sulfate hexahydrate aqueous solution added to sodium hypophosphite monohydrate solution is 60 °C, the morphology of the prepared aluminum hypophosphite is amorphous blocks and mutually bonded spheres. It can be seen that the appropriate dropping temperature has a role in improving the morphology of aluminum hypophosphite. Temperature is the main factor affecting the progress of the reaction. With the increase of the dropping temperature, the speed of crystal nucleation and growth becomes faster, and the difficulty of controlling its slow and uniform growth increases, and the product gradually changes to an amorphous morphology.
[0051] Comparative Example 5 The synthesis of aluminum hypophosphite was as described in Example 1, except that: The temperature when the aluminum sulfate hexahydrate aqueous solution was added dropwise to the sodium hypophosphite monohydrate solution was 90°C.
[0052] If the dropping temperature is too high, the reaction rate will be accelerated, and the particles may not have enough time to form a uniform structure, resulting in uneven crystal growth and increased adhesion between particles. Fig.11 It shows that the morphology of aluminum hypophosphite prepared at a dropping temperature of 90 °C is all amorphous lamellar. The amorphous lamellar morphology indicates that the particles failed to form a regular crystal structure during the reaction, but formed lamellar or layered amorphous substances.
[0053] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing spherical aluminum hypophosphite with a rough surface, characterized in that: The following steps are involved: S1. Add deionized water to aluminum sulfate hexadecahydrate, and stir until the aluminum sulfate hexadecahydrate is completely dissolved to obtain an aluminum sulfate hexadecahydrate aqueous solution; S2, dissolving sodium hypophosphite monohydrate with deionized water and ethylene glycol to prepare a sodium hypophosphite monohydrate solution; S3. Under mechanical stirring conditions, add the aluminum sulfate hexahydrate aqueous solution to the sodium hypophosphite monohydrate solution at a certain temperature, mix them evenly, and heat the water bath to 90°C. The two react to form aluminum hypophosphite; S4. The prepared aluminum hypophosphite slurry is first washed and centrifuged with deionized water, then washed and centrifuged with anhydrous ethanol, vacuum dried, and ground to obtain spherical aluminum hypophosphite.
2. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 1, characterized in that: The microscopic morphology of the spherical aluminum hypophosphite is a spherical structure with a regular morphology and a rough surface formed by stacking small particles.
3. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S1, the concentration of the aluminum sulfate hexadecahydrate aqueous solution is 1.0-3.5 mol / L.
4. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S2, the concentration of sodium hypophosphite monohydrate is 2.58-8.75 mol / L.
5. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S2, the molar ratio of aluminum hypophosphite monohydrate to aluminum sulfate hexadecahydrate is 5-7:
1.
6. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step (2), the volume ratio of the total amount of deionized water used to the amount of ethylene glycol added is 1:
2.
7. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step (1) and step (2), the volume ratio of the total amount of deionized water used to the amount of ethylene glycol added is (1-1.1125):
1.
8. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S3, the dropping temperature is 20-40°C.
9. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S3, the reaction time is 0.5-2 hours, preferably 1 hour.
10. The method for preparing spherical aluminum hypophosphite with a rough surface according to claim 2, characterized in that: In step S3, the mechanical stirring speed is 300-450 rpm.
Citation Information
Patent Citations
A method for preparing nano-aluminum hypophosphite
CN107337187B
Aluminum hypophosphite flame retardant ultrafine powder as well as preparation method and application thereof
CN111689481A
Preparation method of low-sulfur-content and fine-particle-size aluminum hypophosphite and application of low-sulfur-content and fine-particle-size aluminum hypophosphite in PBT (polybutylene terephthalate)
CN118026115A
Cited By
Prismatic aluminum hypophosphite compound as well as preparation method and application thereof
CN121699242A
Prismatic aluminum hypophosphite compound, and preparation method and application thereof
CN121699242B